Strategies for Improving the Effectiveness of Ideological and Political Education for International Students in China-From the Perspective of Refined Management - Wang, Ji (Education Insights, 2026)
In recent years, with the strategic promotion and continuous implementation of the Belt and Road Initiative, international students in China have increasingly become a vital component of the global higher education community. These students not only bring diverse cultural perspectives to Chinese universities but also play a significant role in fostering cross-cultural understanding and academic exchange. Strengthening ideological and political education for international students is therefore of great importance, as it contributes to cultivating high-quality graduates who possess a comprehensive understanding of Chinese culture, values, and social development, while also promoting mutual respect, friendship, and a sense of affinity toward China. From the perspective of refined management, this paper systematically examines the existing challenges in the ideological and political education of international students, including issues related to curriculum content, teaching methods, engagement mechanisms, and the alignment of educational objectives with students’ diverse backgrounds. It further emphasizes the critical role of refined management in enhancing educational effectiveness through targeted planning, personalized guidance, and continuous evaluation. Based on this analysis, the paper proposes a series of practical strategies and improvement measures aimed at optimizing educational practices, strengthening student participation, and improving the overall quality of ideological and political education for international students in China. The findings provide both theoretical insights and practical guidance for higher education institutions seeking to create more effective, inclusive, and culturally responsive educational environments that support the holistic development of international students.